Konsep Pendidikan Agama Islam pada Anak dalam Keluarga Muslim (Studi Kasus pada Sosok Ibu Karir yang Berprofesi Guru) - Manzilatul Hasanah; Abdul Halim (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Looking at the culture that occurs in the environment where we live, most early education is handled by a mother, although there are some fathers who also pay great attention to children's education, but this is still relatively rare and most of the time it is the mother who educates them starting from being able to eat, walk, talk, bathe and etc. Due to the understanding in society that a mother only stays at home without needing to work, the job of earning a living is the father's duty, but in everyday life there are many households where the father's work cannot meet daily needs so the mother must help.In the end, many mothers have outside jobs, mothers are still required to educate their children and earn a living. For mothers, this is an obligation that they must carry out, apart from education in daily life, mothers must also think about psychological and spiritual development, Islamic religion, so that their children have a path that is blessed by Allah SWT.The method that career mothers usually use in educating their children is putting them in TPQ, Islamic boarding school, continuous habituation, parents providing examples. The results obtained from these various efforts are that children get used to praying 5 times a day from childhood, get used to reading the Al-Qur'an, are polite to their parents, behave well towards neighbors, older people or friends and so on.